2022
DOI: 10.1155/2022/1335820
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Application of Augmented Reality in Computerized Skull Base Surgery

Abstract: Cranial base tactics comprise the regulation of tiny and complicated structures in the domains of otology, rhinology, neurosurgery, and maxillofacial medical procedure. Basic nerves and veins are in the nearness of these buildings. Increased the truth is a coming innovation that may reform the cerebral basis approach by supplying vital physical and navigational facts brought together in a solitary presentation. In any case, the awareness and acknowledgment of prospective results of expanding reality frameworks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Furthermore, conventional imaging techniques that focus solely on two-dimensional visual data may suffer from limitations in perceived depth, thereby potentially compromising the practitioner's situational awareness and decision making accuracy. To mitigate such limitations, it is advisable to incorporate depth cues to enhance the perceptual veracity of the rendered images [64]. Additionally, in applications where virtual 3D objects are superimposed onto endoscopic images, it becomes imperative to maintain parallax when the viewing position changes in order to preserve spatial relationships and depth perception.…”
Section: The Digital Surgeonmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, conventional imaging techniques that focus solely on two-dimensional visual data may suffer from limitations in perceived depth, thereby potentially compromising the practitioner's situational awareness and decision making accuracy. To mitigate such limitations, it is advisable to incorporate depth cues to enhance the perceptual veracity of the rendered images [64]. Additionally, in applications where virtual 3D objects are superimposed onto endoscopic images, it becomes imperative to maintain parallax when the viewing position changes in order to preserve spatial relationships and depth perception.…”
Section: The Digital Surgeonmentioning
confidence: 99%
“…The application of Radiomics in oncological diagnostics has emerged as a transformative approach in recent years, particularly in the preoperative assessment of various neoplastic conditions including prostate cancer, lung cancer, and an array of brain tumors such as gliomas, meningiomas, and brain metastases [63][64][65]. Traditional diagnostic methodologies that rely predominantly on qualitative assessments made by radiologists based on "visible" features, Radiomics facilitates the quantitative extraction of high-dimensional features as parametric data from radiographic images [66,67].…”
Section: Data-driven Neurosurgery: Machine Learning Ai-assisted Diagn...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%